Denominationality – (Supra-)Denominationality – (Non-)Denominationality: On the Renaissance Epitaph and Art as a Source of Denominational Identification - Jakubec, Ondřej; Malý, Tomáš (Dějiny – teorie – kritika, 2010)
Th e three presented texts are a contribution to the discussion on denominationality in the 16th and 17th centuries. Using the example of Renaissance epitaphs the authors consider the extent to which denominational meanings may be observed in early modern works of art and the limits of such observations. The introductory text presents a more general (historiographical) view of the prerequisites for the construction of a denominational identity in the Czech lands and of Renaissance epitaphs as a specifi c „medium“. Both authors admit that the epitaphs contain many denominational connotations, but at the same time both are aware of numerous weaknesses in a denominationally focused interpretation of the works in question, particularly in relation to their special function as commemorative devices. In this respect the texts diff er in the extent to which the authors recognize denominational aspects in these works of art: while the fi rst text (by O. Jakubec) places greater stress on the denominational context in the overall broad meaning of a Renaissance epitaph, the second text (by T. Malý) is more cautious, with a particularly sceptical approach towards attempts to view these works as denominationally distinct.